Strangers in a Strange Land Occidentalist Publics and Orientalist Geographies in Nineteenth‐Century Georgian Imaginaries - Manning, Paul (Cultural Revolutions: Russia in the Twentieth Century, 2012)
In this text Manning examines the formation of nineteenth-century intelligentsia print publics in the former Soviet republic of Georgia both anthropologically and historically. At once somehow part of "Europe," at least aspirationally, and yet rarely recognized by others as such, Georgia attempted to forge European style publics as a strong claim to European identity. These attempts also produced a crisis of self-definition, as European Georgia sent newspaper correspondents into newly re-conquered Oriental Georgia, only to discover that the people of these lands were strangers. In this encounter, the community of "strangers" of European Georgian publics proved unable to assimilate the people of the "strange land" of Oriental Georgia. This crisis produced both notions of Georgian public life and European identity which this book explores.